2020
DOI: 10.1109/jeds.2020.3022180
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interface Traps on Negative Capacitance Transistor: Device and Circuit Reliability

Abstract: In this work, we investigate the impact of Si-SiO2 interface traps on the performance of negative capacitance transistor, which is a promising emerging technology that aims at achieving a steep sub-threshold slope. Interface traps induced degradation is well known to be one of the major concerns when it comes to reliability. We focus on investigating the impact of different interface trap concentrations on the figures of merit of both the devices and circuits. Our investigation is performed using TCAD models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…1) Bias Temperature Instability (BTI), i.e., V th shift due to charge trapping, plays a role in FeFETs [30], [57] as well as NCFETs [46], [48]. V th -shifts due to BTI can either cause fast, recoverable issues [30], [57] (i.e., causing instability) or permanent damage (related to trap generation) limiting reliability [28], [35], [40], [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) Bias Temperature Instability (BTI), i.e., V th shift due to charge trapping, plays a role in FeFETs [30], [57] as well as NCFETs [46], [48]. V th -shifts due to BTI can either cause fast, recoverable issues [30], [57] (i.e., causing instability) or permanent damage (related to trap generation) limiting reliability [28], [35], [40], [46].…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in [48], due to the internal voltage amplification NCFETs would be more prone to interface trap generation than the corresponding MOSFETs (i.e., at the same node without the ferroelectric layer) if operated at the same supply voltage. On the other hand, at a given interface trap concentration (or equivalently, stress time) NCFETs have lower ΔV th than MOSFETs 6 [48], as also explained previously. Hence, in practice NCFETs should be operated at lower supply voltage than their MOSFETs counterparts to slow down aging.…”
Section: Nbti-free Operation In Ncfetsmentioning
confidence: 98%
“…(3) Interface Traps Effects: In [36], we studied the impact of interface traps on the device characteristics of NCFET compared to the baseline transistor using calibrated TCAD simulations. Our analysis showed that, at the same interface trap concentration, the NCFET always exhibits less degradation than the baseline transistor due to the better electrostatic integrity caused by the negative capacitance effect.…”
Section: Ncfet Reliability Discussionmentioning
confidence: 99%
“…Recently, an NC GAA-FET having a metal-ferroelectric-insulator-semiconductor (MFIS) type has been investigated by introducing NC characteristics to a gate stack as a nextgeneration semiconductor in a GAA transistor [19,20]. In addition, it has been reported that interface traps at the Si-SiO 2 interface can result in the degradation of transistor performance (e.g., sub-threshold swing) [21], the process-variable ∆V th [22], and negative bias temperature instability (NBTI)-induced ∆V th [23]. This interface trap effect has been considered important from before in silicon GAA-FET without ferroelectric material, and compact modeling methodologies have been proposed [24].…”
Section: Introductionmentioning
confidence: 99%